Sosiologi Lembaga Pendidikan Sekolah Menengah Pertama Islam Di Wilayah Perbatasan: Studi Ketimpangan Akses Dan Kualitas Pendidikan - Meli Astutianingsih; Muh Hanif (Advances In Education Journal, 2026)
Inequalities in access to and quality of education are serious issues at SMP IT Nusantara Kembaran, characterized by inadequate facilities, a shortage of teachers and textbooks, and low parental economic capacity. This study aims to identify the factors causing inequalities in access to and quality of education at SMP IT Nusantara Kembaran. This study employs a phenomenological qualitative approach through observation, in-depth interviews, and document analysis involving teachers, students, parents, and community leaders. The findings reveal that these inequalities stem from an imbalanced teacher-to-student ratio and a lack of learning resources. Consequently, students drop out due to financial constraints, face learning difficulties from sharing textbooks, experience diminished motivation to learn, and encounter limited access to transportation to school. This study concludes that these inequalities have the potential to perpetuate intergenerational social disparities, thus requiring affirmative policies and more participatory school management.